12-(-x+10)=566

Simple and best practice solution for 12-(-x+10)=566 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-(-x+10)=566 equation:


Simplifying
12 + -1(-1x + 10) = 566

Reorder the terms:
12 + -1(10 + -1x) = 566
12 + (10 * -1 + -1x * -1) = 566
12 + (-10 + 1x) = 566

Combine like terms: 12 + -10 = 2
2 + 1x = 566

Solving
2 + 1x = 566

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 1x = 566 + -2

Combine like terms: 2 + -2 = 0
0 + 1x = 566 + -2
1x = 566 + -2

Combine like terms: 566 + -2 = 564
1x = 564

Divide each side by '1'.
x = 564

Simplifying
x = 564

See similar equations:

| 5(2x-1)=7(x) | | 5/4x=0 | | 3(x-3)-6(x+3)=4(2x-3)-8(2x+3) | | 1-9x^2+8x^3=0 | | 28-y=18 | | 1306.7424=4*3.14*r^2 | | 5=-1/4x | | 0=R^2-312.12 | | (0.1333+y)-0.2333=0.1 | | 0=6.28r^2+19.468r-25.748 | | 1/8*7/8 | | -2(-6-16)=2c-16 | | 9log^3(6-2x)+21=35 | | 110x+0.40=50x+0.60 | | -5/9=-x/4 | | Y^2-25y+144=0 | | 67+25x=300x | | -x^2+7x+8=0 | | 36x^2+48x+16=7(-6x-4)-12 | | n^2=-20+9n | | 0=6.28r^2+81.64r-453.6672 | | 5/16 | | s=4/3*3.14*15.3^3 | | (-x/2)=(3/5) | | 30x3.14/180 | | a+3a-7a= | | -26/32 | | 0=6.28r^2+253.712r-3668.838 | | 9.6-(2.6-y)=4 | | 19x+2=37 | | 2n-24=12 | | 6r^2-11r+5=0 |

Equations solver categories